La etnia Chilcho y su enclave de mitmas en Cajamarca, siglos xv-xx - Espinoza Soriano, Waldemar (2006)
The Etnohistoria is a discipline that continuous being developed in Peru. The location and the examination of new written by hand sources early, the microregional bibliography search and the direct route of the spaces still studied continue practicing to recover the structural patterns and the daily life of the Andean towns between centuries XV and XX. The author reviews the singular case of the sociopolítica experience lived by the Chilcho ethnic group (Cajamarca) and his relations on conflict and adaptation with the Empire Inca and the Republic.